PERFORMANCE EVALUATION OF REFRIGERANTS: R717, R290, R134A, R22 AND R712 (CAHIERS MAGELLANES-NS, 2024)
The main focus of the research is analysis of the function of the refrigerants such as R717 (ammonia), R290 (propane), R134a (1,1,1,2- tetrafluoroethane), and R22 (dichlorodifluoromethane). The paper has analyzed and compared the efficiency factors, energy efficiency ratios, thermodynamic properties, and environmental effects. After lots of research, it has been ascertained that R134a has no implication on the depletion of the ozone layer. Furthermore, the high GWP was expressed to attract specific concerns about the ecological significance of this substance. The cause of disappearance of R22 is due to its features such as ODP leading to its elimination from use. Thus, besides having a zero GWP and being even more efficient than R744, R717 had to meet high requirements on safety due to toxicity and flammability factors. On the other hand, R290 while being very efficient as a ‘‘natural’’ although flammable refrigerant has now been considered as an optimal choice while exercising certain handling precaution since GWP is low . Altogether, the research has elucidated why the choice of refrigerants or their characteristics should meet specific application requirements and conditions or environmental factors. Last but not the least it has helped to promote a shift towards ecological refrigerants and air conditioning systems.